Importance of proper nutrition during pregnancy - Vuković V.; Popović J.; Resimić R. (Association of Nurses Technicians and Midwives, 2016)
Introduction: Nutrition during pregnancy is very important for the health of pregnant women and normal development of the child. Proper nutrition during pregnancy means that pregnant women eat better quality foods. The increase in the need for additional calories grows in the fourth month of pregnancy by about 300 kcal / day. Calorie intake in the third trimester should be increased by about 400 kcal / day. Objective: To determine the level of awareness of pregnant women about the importance of proper nutrition during pregnancy. Methodology: Descriptive and observational method-poll survey was conducted in a population of pregnant women. The survey was conducted on a random sample of 100 N-. A specifically created questionnaire was used which represented an improved version of the Questionnaire for assessing the proper nutrition during pregnancy. Results: Based on the obtained data, 65% of pregnant women during pregnancy gained between 10-15 kg, a large number of examinees, 97%, said it was very important to maintain the weight in the normal range. According to collected data, 58% of the pregnant women adhere to hygienic-dietary regimen during pregnancy. 97% of pregnant women thought that in pregnancy they should eat for two, while 3% of women thought the opposite. Results show that 79% of women regularly use vegetables in their diet. According to collected data, we see that 90% consumed fruit, while 10% of pregnant women do not consume fruit daily. An alarming indicator is that 63% of examinees intake fats of animal origin, while 37% of pregnant women consume vegetable oil. Conclusion: During the research, 100% of the surveyed pregnant women consider that proper nutrition is of great importance for pregnancy. Bearing in mind that the testing was anonymous and that the pregnant women still are expected to give birth, the results are excellent. Therefore it is very important to raise awareness of proper nutrition during pregnancy and during lactation and that expectant mothers learn to resist the pressures of adopting harmful behaviors.